2015
DOI: 10.4236/jbm.2015.36003
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Stigma of Mental Illness: Path Analysis Conducted with Amos in Transcultural Psychiatry in Australia

Abstract: Aim: The study was designed to elucidate the relationships between cultural values, contact level, differential nursing practices and stigma towards mental illness among General and Psychiatric Nurses (N = 208) from Anglo and Chinese backgrounds in Australia. The study results aimed at informing education disciplines, health care providers and policy makers to examine strategies that seek to diminish stigma of mental illness and to reflect on cultural sensitive issues associated with mental illness. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Overall results suggest that Chinese immigrants endorsed a stronger collectivist values than individualist values which correlate positively with the literature which commented that Chinese people maintained collectivist values though living in Western nations [8] [14]. The finding indicated that participants endorsed more collectivist value (37.7% (CFC) + 90.6% (CFI) = 128.3%) than individualist value (60.1% (ISA) + 33.3% (ISO) = 93.4%).…”
Section: Discussionsupporting
confidence: 77%
“…Overall results suggest that Chinese immigrants endorsed a stronger collectivist values than individualist values which correlate positively with the literature which commented that Chinese people maintained collectivist values though living in Western nations [8] [14]. The finding indicated that participants endorsed more collectivist value (37.7% (CFC) + 90.6% (CFI) = 128.3%) than individualist value (60.1% (ISA) + 33.3% (ISO) = 93.4%).…”
Section: Discussionsupporting
confidence: 77%
“…Chinese nurses, particularly general nurses, were shown to endorse more highly social distancing towards those with mental illness and contact was placed as a mediator for this attitude (Ku, Ha & Siriwan, 2015) [18]. Results suggest a relationship between culture and stigma, specifically among Chinese nurses but do not clarify why, such a relationship exists [19].None of the previous studies quoted earlier effectively show cultural differences in stigma as they mainly dealt with within-culture depiction of social distancing towards people with a mental illness. This had prompted the first author, Ku, to design the Attitudes towards Depression and Schizophrenia Scale (ADSS) to measure Chinese Australian Community Attitudes towards Mental Illness (Ku& Ha, 2015) [20].…”
Section: Discussionmentioning
confidence: 80%
“…What has been of light is that among the 208 nurses, Chinese nurses reported less contact with mental illness than Anglo nurses, contact level was better placed as a mediator between stigmatising attitudes and differential clinical approaches among the 84 Chinese immigrant nurses in Australia using structural equation modelling, when Chinese cultural values, as a latent variable, was analysed using path analyses (2015) [16]. Subsequently, the first author (Ku) has embarked on a PhD study which comprised both quantitative and qualitative design by not involving Anglo-culture participants, but to further examine what specifically constitutes stigma of mental illness in the wider Chinese community, focusing on uncovering socio-cultural factors influencing Chinese people's attitudes towards depression and schizophrenia, two commonly known mental disorders (2015) [17].…”
Section: Methodsmentioning
confidence: 99%